Effect of Organic Modifier Types on the Physical–Mechanical Properties and Overall Migration of Post-Consumer Polypropylene/Clay Nanocomposites for Food Packaging - Guarda-Moraga, A; Valenzuela-Bascunan, X; Galotto-Lopez, M; Lopez de Dicastillo-Bergamo, A; Garrido-Ayala, L; Velasquez, E (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The deterioration of the physical–mechanical properties and loss of the chemical safety of plastics after consumption are topics of concern for food packaging applications. Incorporating nanoclays is an alternative to improve the performance of recycled plastics. However, properties and overall migration from polymer/clay nanocomposites to food require to be evaluated case-by-case. This work aimed to investigate the effect of organic modifier types of clays on the structural, thermal and mechanical properties and the overall migration of nanocomposites based on 50/50 virgin and recycled post-consumer polypropylene blend (VPP/RPP) and organoclays for food packaging applications. The clay with the most hydrophobic organic modifier caused higher thermal stability of the nanocomposites and greater intercalation of polypropylene between clay mineral layers but increased the overall migration to a fatty food simulant. This migration value was higher from the 50/50 VPP/RPP film than from VPP. Nonetheless, clays reduced the migration and even more when the clay had greater hydrophilicity because of lower interactions between the nanocomposite and the fatty simulant. Conversely, nanocomposites and VPP/RPP control films exhibited low migration values in the acid and non-acid food simulants. Regarding tensile parameters, elongation at break values of PP film significantly increased with RPP addition, but the incorporation of organoclays reduced its ductility to values closer to the VPP. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.